Transparency without accountability - Mwangi wa Githinji; Frank Holmquist (University of Massachusetts, Department of Economics, 2011)
Kenya has been going through a period of political reform from 1991 when section 2A of the constitution that had made Kenya a de jure one party state was repealed. The reform followed a prolonged struggle by citizens both within and without the country. Their call for democracy was one that, post the fall of the Berlin wall, was embraced by western countries. Via diplomatic pressure and conditionality on aid, western donors played an important role in the repeal of section 2a, the return of multi-party elections and in the creation and reform of a number of political institutions and offices. In the main these changes were pushed by the donors and though supported by the opposition in Kenya they did not rise organically from the struggle over political power in Kenya. In this paper, we argue that although these reforms led to a heightened awareness of the ills of the political class, they failed to actually hold members of this class accountable for their transgressions. We argue that these institutions presupposed the existence of an electorate with an effective set of identities that belonged to the larger Kenyan nation. This broader construct of society did not exist. A history of economic and political inequality from the inception of modern Kenya had resulted in a divided population that was unable to exercise this mandate, and could ultimately discipline politicians when they failed. In actuality, since the politics was not based on broader Kenyan national interests but rather narrower personal interests construed as ethno-nationalist, the political class was not accountable to the larger Kenyan constituency.
Keywords: 330